RANBP2 Activates O-GlcNAcylation through Inducing CEBPα-Dependent OGA Downregulation to Promote Hepatocellular Carcinoma Malignant Phenotypes - Liu, Xiaoming (Cancers (Basel), 2021)
SIMPLE SUMMARY: Hepatocellular carcinoma (HCC) is characterized by a poor prognosis and high mortality rate, with complex molecular alterations, including glycosylation. O-linked N-acetylglucosamine (O-GlcNAc) is a dynamic modification process jointly controlled by the “writer” O-GlcNAc transferase (OGT) and “eraser” O-GlcNAcase (OGA), and an increase in total O-GlcNAc correlates with advanced malignant HCC phenotypes. The aim of our study was to explore the potential regulatory patterns underlying the OGT/OGA imbalance that contributes to HCC malignancies. We confirmed that RANBP2, one of the SUMO E3 ligases, downregulates OGA transcription while not affecting OGT. As a transcriptional factor positively regulating OGA, CEBPα was also SUMOylated and destabilized by RANBP2. Our in vitro and in vivo studies provide evidence of RANBP2 downregulating OGA and thus triggering O-GlcNAcylation in a CEBPα-dependent manner. The subsequent hyper-O-GlcNAcylation of protein substrates such as PGC1α via the RANBP2–CEBPα–OGA pathway may represent a pharmaceutical strategy for HCC treatment. ABSTRACT: O-GlcNAcylation is an important post-translational modification (PTM) jointly controlled by O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Aberrant hyper-O-GlcNAcylation is reported to yield hepatocellular carcinoma (HCC) malignancy, but the underlying mechanisms of the OGT/OGA imbalance responsible for HCC tumorigenesis remain largely unknown. Here, we report that RAN-binding protein 2 (RANBP2), one of the small ubiquitin-like modifier (SUMO) E3 ligases, contributed to malignant phenotypes in HCC. RANBP2 was found to facilitate CCAAT/enhancer-binding protein alpha (CEBPα) SUMOylation and degradation by direct interplay with CEBPα. As a transcriptional factor, CEBPα was verified to augment OGA transcription, and further experiments demonstrated that RANBP2 enhanced the O-GlcNAc level by downregulating OGA transcription while not affecting OGT expression. Importantly, we provided in vitro and in vivo evidence of HCC malignant phenotypes that RANBP2 triggered through an imbalance of OGT/OGA and subsequent higher O-GlcNAcylation events for oncogenic proteins such as peroxisome proliferative-activated receptor gamma coactivator 1 alpha (PGC1α) in a CEBPα-dependent manner. Altogether, our results show a novel molecular mechanism whereby RANBP2 regulates its function through CEBPα-dependent OGA downregulation to induce a global change in the hyper-O-GlcNAcylation of genes, such as PGC1α, encouraging the further study of promising implications for HCC therapy.